A39 Tangible and perceptual factors on active travel by children: Quebec City case study. Issue 2 (June 2015) - Maranda, Antoine; Waygood, Edward
Abstract: Background: Many western countries have experienced a significant drop in children's active transportation rates. Previous research shows that many of the factors that influence children's active transports are tangibles (residential density, mixed activity etc.), while others are more related to perceptions (neighbourhood safety, social norms, etc.). These two types of factors are part of a matrix of influences ultimately leading to the child's transport mode but, few studies have quantified the respective weights of tangible and perceptual factors in children's modal choice. Thus, this study aims to explore if the likelihood that a child makes a trip by an active mode of transport depends more on tangible or perceptive factors. Methods: In the fall of 2014, questionnaires were distributed in ten fifth grade classes from six primary schools located in peri-urban (2), suburban (2) and central neighbourhoods (2) of Quebec City. These questionnaires consist on a trip diary, in which the children reported all their trips for the previous two days, for a total of more than 750 trips by 213 children. The proportion of active trips (AT%) by each school's urban category (peri-urban, suburban, or central) were compared using chi-squared test of independence to determine whether differences existed by built environment. WalkScore, a measure of the walkability of a location (associated with each child's postal code), was used as a proxy for the tangible factors and the right to independent mobility (IM) associated with each child represented the perceptual factors. Logistic regressions were then used to examine how actives trips were influenced by tangible (WalkScore) and perceptual (IM) factors. Results: After preliminary analysis on three schools, it is noted that AT% respectively accounts for 25%, 52% and 82% of trips recorded in peri-urban, suburban and central neighbourhoods. Secondly, the results indicate a strong correlation between IM and AT% (OR: 3.3) when the three school are analysed simultaneously. Separately, the correlation is highest in the suburban neighbourhood and non-significant in the peri-urban and central districts. Similarly, WalkScore and AT% show a clear correlation (OR: 1.035) when taken globally, but a significant correlation is found only for the central neighbourhood school when each is analysed separately. Conclusions: These preliminary results show that in our case study, tangible and perceptual factors seem to influence active transportation on a different degree, according to which type of neighbourhood is taken into account. The results of the complete study are still under analysis at the moment.